Cultural Insecurity and Social Anxiety: The Mediating Role of Identity Uncertainty - Anderson, Michael; Nishimura, Haruka (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to examine the mediating role of identity uncertainty in the relationship between cultural insecurity and social anxiety among adults in the United States. Methods and Materials: The study employed a descriptive correlational design and included 430 adult participants from the United States, selected based on the Morgan and Krejcie sample size table. Standardized tools were used to assess cultural insecurity, identity uncertainty, and social anxiety. Data were analyzed using Pearson correlation in SPSS-27 and structural equation modeling (SEM) in AMOS-21 to test both direct and indirect relationships between variables and evaluate the model fit. Findings: The results showed significant positive correlations among cultural insecurity, identity uncertainty, and social anxiety (r = .53 to .62, p < .001). Structural equation modeling confirmed that identity uncertainty significantly mediated the relationship between cultural insecurity and social anxiety. The model demonstrated good fit indices (χ² = 134.28, df = 74, χ²/df = 1.81, RMSEA = 0.043, CFI = 0.97, TLI = 0.95). The total effect of cultural insecurity on social anxiety was strong and significant (β = .70, p < .001), with both direct (β = .34, p < .001) and indirect effects via identity uncertainty (β = .36, p < .001) contributing to this relationship. Conclusion: The findings highlight the psychological pathway through which cultural insecurity leads to social anxiety by increasing individuals’ identity uncertainty. This underscores the importance of addressing identity-related stress in interventions aimed at reducing social anxiety, especially in culturally diverse and shifting environments. Efforts to promote cultural inclusion and strengthen identity coherence may serve as protective factors against social withdrawal and emotional distress.